STUDI KORELASI KETERAMPILAN ARGUMENTASI ILMIAH SISWA KELAS VIII SMP NEGERI DI KOTA PONTIANAK - Jevania, Jevania; Tenriawaru, Andi Besse (Universitas Tanjungpura, 2023)
This research refers to Toulmin's Argument Pattern (TAP) that have components including claims, data, evidence, support, qualifications, and disclaimers. This research is conducted with the objective of understanding the relationship or correlation of scientific argumentation skills with each indicator that refers to Toulmin's theory. This research was conducted by distributing test questions based on the Toulmin indicator, carried out through 3 stages, such as preparation, to prepare scientific argumentation questions, the implementation test questions with class VIII students in Pontianak City and reporting to find out the relationship between results of scientific arguments and each Toulmin indicators. The data analysis method employed is a descriptive quantitative analysis approach, which involves presenting the data through score distributions and predefined rating scale categories. Furthermore, the analysis utilizes the SPSS 21 software to determine the correlation between scientific skills and individual indicators. The findings indicated that the relationship among the results of scientific argumentation on the data indicators was 0.028, the relationship with the qualification indicator was 0.191, the relationship with the claims indicator was 0.002, the relationship with the support indicator was 0.000, the relationship with the refutation indicator was 0.003, and relationship with the evidence indicator was 0.029. Based on the value of the relationship on each indicator. It can be reduced that there exists a distinct correlation between each indicator and the outcomes of scientific arguments.